Prospective randomized trial evaluating blood and prostate tissue concentrations of green tea polyphenols and quercetin in men with prostate cancer. Issue 5 (29th April 2020) - Henning, Susanne M.; Wang, Piwen; Lee, Ru-Po; Trang, Amy; Husari, George; Yang, Jieping; Grojean, Emma M.; Ly, Austin; Hsu, Mark; Heber, David; Grogan, Tristan; Li, Zhaoping; et al.
Abstract : Epigallocatechin gallate, epicatechin gallate (Green Tea Polyphenols – GTPs) and quercetin (Q) were taken up in prostate tissue after Q and GTP consumption. Our findings herein suggest a potential effect of Q on GTP metabolism. Abstract : We evaluated if chronic consumption of quercetin (Q) with green tea extract (GTE) enhances the bioavailability of GT polyphenols (GTPs) and reduces methylation activity as previously observed in mouse xenograft tumors. In this prospective, randomized, parallel design, placebo controlled study, thirty-one men with prostate cancer consumed daily 1 gram of GTE (830 mg of GTP) with 800 mg of Q (GT + Q) or placebo (GT + PL) for four weeks before prostatectomy. First morning voided urine was collected at baseline, 3 weeks and the day of surgery, and prostate tissue on the day of surgery. In week 3, plasma concentration of GTPs and Q was measured in blood collected before and 2 hours after the morning dose. Prostate tissue epigallocatechin gallate (EGCG) and epicatechin gallate (ECG) were detected in 67 and 93% of participants in the GT + Q group and 75 and 94% of participants in the GT + PL group. Q was increased 14-fold, 12-fold and 4.5-fold in plasma, urine, and prostate tissue, respectively, in the GT + Q compared to the GT + PL-group. There was a trend for decreased EGC levels in urine collected prior to prostatectomy in the GT + Q compared to GT + PL-group ( p = 0.053). Plasma epigallocatechin (EGC) showed a trend to increase ( p = 0.066) two hours after capsule intake in the GT + Q vs. the GT + PL-group. There was no significant difference between the groups in GTP content or methylation activity in prostate tissue or RBCs. No liver toxicity was observed. Although our findings are suggestive, further studies are warranted evaluating if Q alters GTP metabolism.